Review of decisions in cases of administrative offenses for violation of the order of organizing and holding meetings, rallies, street marches and demonstrations under the legal regime of martial law - M. A. Sambor (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the peculiarities of the law enforcement practice of courts of appeals when reviewing decisions in cases on appeals in cases of administrative offenses for violation of the order of organizing and holding meetings, rallies, street marches and demonstrations under the conditions of the legal regime of martial law in Ukraine. Attention is drawn to the quality of argumentation of decisions in cases of administrative offenses for violation of the order of organizing and holding meetings, rallies, street marches and demonstrations under the conditions of the legal regime of martial law in Ukraine. Special attention is paid to the conditions of use and exercise of the right to freedom of peaceful assembly. The issue of forming a unified legal position regarding the application of positive law norms to regulate the use and exercise of the right to freedom of peaceful assembly under the conditions of the legal regime of martial law is being investigated. The specifics of the argumentation of decisions made by appeal courts in cases of administrative offenses are analyzed, in particular the specifics of the exercise of the right to freedom of peaceful assembly under the conditions of the legal regime of martial law and the influence of such a legal regime on the application of administrative responsibility for violating the order of organizing and holding meetings, rallies, street marches and demonstrations.